Curcumin reduces prostaglandin E2, matrix metalloproteinase-3 and proteoglycan release in the secretome of interleukin 1β-treated articular cartilage - Clutterbuck, Abigail L.; Allaway, David; Harris, Pat; Mobasheri, Ali (F1000Research, 2013)
Objective: Curcumin (diferuloylmethane) is a phytochemical with potent anti-inflammatory and anti-oxidant properties, and has therapeutic potential for the treatment of a range of inflammatory diseases, including osteoarthritis (OA). The aim of this study was to determine whether non-toxic concentrations of curcumin can reduce interleukin-1beta (IL-1β)-stimulated inflammation and catabolism in an explant model of cartilage inflammation. Methods: Articular cartilage explants and primary chondrocytes were obtained from equine metacarpophalangeal joints. Curcumin was added to monolayer cultured primary chondrocytes and cartilage explants in concentrations ranging from 3μM-100μM. Prostaglandin E2 (PGE2) and matrix metalloproteinase (MMP)-3 release into the secretome of IL-1β-stimulated explants was measured using a competitive ELISA and western blotting respectively. Proteoglycan (PG) release in the secretome was measured using the 1,9-dimethylmethylene blue (DMMB) assay. Cytotoxicity was assessed with a live/dead assay in monolayer cultures after 24 hours, 48 hours and five days, and in explants after five days. Results: Curcumin induced chondrocyte death in primary cultures (50μM p<0.001 and 100μM p<0.001) after 24 hours. After 48 hours and five days, curcumin (≥25μM) significantly increased cell death (p<0.001 both time points). In explants, curcumin toxicity was not observed at concentrations up to and including 25μM after five days. Curcumin (≥3μM) significantly reduced IL-1β-stimulated PG (p<0.05) and PGE2 release (p<0.001) from explants, whilst curcumin (≥12μM) significantly reduced MMP-3 release (p<0.01). Conclusion: Non-cytotoxic concentrations of curcumin exert anti-catabolic and anti-inflammatory effects in cartilage explants.